Personality features of patients with alcohol use disorders - Akvardar, Yıldız; Arkar, Haluk; Akdede, Berna B.; Gül, Selami; Sarı, Özden; Tunca, Zeliha (Journal of Dependence, 2005)
Objective: It is aimed to determine the discriminating personality characteristics of patients with alcohol use disorders compared to healthy control subjects.Method: Cloninger’s Temperament and Character Inventory (TCI) was employed to the patients with a diagnosis of alcohol use disorder meeting the DSM-IV criteria (n = 31) and their personality profiles were compared with age and gender matched non-psychiatric healthy control subjects (n = 31).Results: Patients with alcohol use disorder were characterized by higher rates of novelty-seeking and harm avoidance. Patients scored lower on reward dependence, persistence, self-directedness, and cooperation. The differences in novelty-seeking, harm avoidance, persistence and self-directedness between patients and control group were found to be statistically significant. Self-directedness was the most important discriminative variable in the dicrimina-tive function analysis.Conclusion: Higher novelty-seeking is related to im-pulsivity, and is considered to be important at the onset of drug taking behavior. High harm avoidance is related to shyness, social inhibition, fear of uncertainity, and pessimistic worry in anticipation of problems. These negative feelings may be comforted by alcohol, whereas heavy alcohol use may lead to dependence. Individuals with low persistence tend to give up easily when faced with frustration. Lower self-directedness was reported as indicating a higher probability of personality disorder. Determining personality profile among patients with alcohol use disorders may be useful in employing different treatment approaches and evaluating the treatment outcome.
Keywords: Alcohol use disorders; personality characteristics; temperament; character